Tracking Control of an Electro-Hydraulic Actuator System using LQR Controller - Ishak, Norlela; Kamarudin, Ahmad Zikri; Adnan, Ramli (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Electro-Hydraulic actuator (EHA) is a one type of application used in industry and building high performance of motion control process. Apparently, dealing with EHA behaviour is quite difficult and make the controlling process complicated. Designing Linear Quadratic Regulator (LQR) controller as a feedback controller require in selecting the weighting parameter Q and R. The result shows that the higher value of Q offers fast response and high stability by referring the placement of close-loop poles. However, the higher value of Q gives a higher error that can make position performance of hydraulic actuator become worst. In order to overcome this problem, the feedforward controller is developed by implementing the zero-phase error tracking control (ZPETC). It shows that both feedforward and feedback controller offers good tracking position performance in reducing gain and phase error.